Impact of Climate Change on Crop and Dairy Farming in Telangana: Agricultural Scientists Perspective (Indian Journal of Extension Education, 2024)
Climate change has comprehensive consequences on agriculture and livestock that will directly impact farmers, the perception of Agricultural scientists concerning climate change regionally is crucial in addressing its negative impacts effectively, thus the study was purposively conducted in the state of Telangana during 2021-2022 in nine major Indian institutes viz., ICRISAT, CRIDA, IIMR, IIOR, NIPHM, PJTSAU, NAARM, NIRD & PR, and MANAGE to assess the perception of Agriculturalscientists on causes of climate change, changes in climatic parameters, and on the impact of climate change on crop and dairy farming, random sampling procedure was followed and the total respondents for the study was 150. Pre-tested and standardized interview schedules were used to obtain data. The study through scientists’ perception identified the most important causes of climate change, the most observed changes in climatic parameters, and, the greatest impact of climate change on crop and dairy farming. The composite index developed using Principal Component Analysis showed that most of the respondents had a medium level of perception. Thus, the perceptions of agricultural scientists should be tapped to their fullest potential by policymakers in framing suitable solutions for adverse climate change impacts.